Research Development on Horseshoe Crab: A 30-Year Bibliometric Analysis - Luo, Zhen; Miao, Fengze; Hu, Menghong; Wang, Youji (Frontiers in Marine Science, 2020)
This review provides updated information and analysis about research development of horseshoe crabs during past 30 years, and raises some suggestions for future studies of horseshoe crabs. Horseshoe crab is a unique marine species and attracts many scholars in various research fields. However, from the bibliometric point, to date, research development of horseshoe crabs has not been analyzed and reported. Bibliometric analysis is a unique tool to evaluate the development in a certain research area by analyzing relevant publications and researchers all over the world. In this study, Web of Science, Google Scholar and PubMed were used to collect relevant data of horseshoe crab. To visualize the cooperation and hot keywords in this field, the software, VOSviewer was used. From 1989 to 2019, scholars focus more on the physiology, medical value and ecological conservation in horseshoe crab study. The ongoing development of some topics in this field is not so fast for some reasons which are explained in this review. Some important or recent studies were discussed and some potential hot research spots were suggested for the future research.